Museum: Media of Non-Formal Education in Intruding Character Values Strengthening the National Self - Ida Bagus Brata; Ida Bagus Rai; Lianda Dewi Sartika; Ida Bagus Nyoman Wartha (Mimbar Ilmu, 2022)
Museums are scientific information service providers based on data and facts presented through collections as part of a scientific study. This study aims to analyses museum as a medium of non-formal education in instilling character to strengthen national identity. The study in this paper is classified as a descriptive-exploratory type of study. This study uses a literature review approach and data study through the internet network, combined with field studies by visiting the Bali Museum as a research locus where cultural heritage is stored. Data analyses divided into three stages, namely: data reduction, data presentation, concluding/verification. The study results show that museums are perceived as non-profit institutions that prioritize social goals, such as education. Museums as a place for cultural studies while having recreation can foster thinking skills in children. The eyes are the windows to the soul that can stimulate active, creative, critical, and innovative thinking, thus giving rise to intelligence in understanding the character values ​​that lie behind a collection of cultural heritage to strengthen national identity. The Bali Museum is the pride of the Balinese people having a fundamental role in instilling character values ​​in maintaining national identity and identity.